Measurement of Sarcopenia in Head and Neck Cancer Patients and Its Association With Frailty - de Bree, Remco; Meerkerk, Christiaan D. A.; Halmos, Gyorgy B.; Mäkitie, Antti A.; Homma, Akihiro; Rodrigo, Juan P.; López, Fernando; Takes, Robert P.; Vermorken, Jan B.; Ferlito, Alfio (Frontiers in Oncology, 2022)
In head and neck cancer (HNC) there is a need for more personalized treatment based on risk assessment for treatment related adverse events (i.e. toxicities and complications), expected survival and quality of life. Sarcopenia, defined as a condition characterized by loss of skeletal muscle mass and function, can predict adverse outcomes in HNC patients. Skeletal muscle mass (SMM) measurement only is often used to determine if sarcopenia is present or not. SMM is most often assessed by measuring skeletal muscle cross-sectional area on CT or MRI at the level of the third lumbar vertebra. As abdominal scans are not always available in HNC patients, measurement of SMM at the third cervical vertebra has been developed and is frequently used. Frailty is a highly prevalent age-related condition which is also associated with adverse outcomes. There is no international standard measure of frailty and there are multiple measures of frailty. Depending on the definitions used for sarcopenia and frailty, there is more or less overlap between both conditions. However, it has yet to be determined if sarcopenia and frailty can be used interchangeably or that they have additional value and should be used in combination to optimize individualized treatment in HNC patients.